Analisis Pesan Moral dalam Film Ngeri-Ngeri Sedap Melalui Pendekatan Semiotika Roland Barthes - Br Sianturi, Norima; Siburian, Panigoran; Br. Ginting, Sri Dinanta (Medan Resource Center, 2025)
This study examines the moral messages embedded in the Indonesian film Ngeri-Ngeri Sedap through the lens of Roland Barthes’ semiotic theory. As a culturally significant cinematic work, the film reflects the familial tensions and sociocultural dynamics of the Batak community. The research addresses the central question: how are moral values constructed and communicated via signs, codes, and myths within the film’s narrative and visual elements? Employing qualitative content analysis and Barthes’ two-level signification model—denotation and connotation—the study analyzes selected scenes, dialogues, and character interactions. The findings indicate that moral themes such as parental expectations, communication gaps, cultural identity, and reconciliation are conveyed through symbolic representations, traditional practices, and dramatic conflicts. These semiotic expressions function within a broader ideological discourse, reinforcing the importance of empathy, mutual respect, and intergenerational understanding. The study concludes that Ngeri-Ngeri Sedap utilizes a multilayered semiotic structure to deliver implicit moral commentary, offering critical insights into Indonesian familial and cultural narratives. This research contributes to the field of media studies by demonstrating the efficacy of semiotic analysis in uncovering deeper ideological meanings in contemporary film.